Women’s Pathways to Crime: A Heuristic Typology of Offenders - DeHart, Dana (Criminal justice and behavior, 2018)
The current study proposes a heuristic model for classification of female offenders into groups based on key variables relevant to women’s backgrounds and programming needs. We utilize a mixed-methods approach with a sample of 60 women incarcerated in a maximum-security prison. We develop qualitative, person-centered groupings of female offenders, and then use quantitative analyses to provide more detailed data on each group. Findings demonstrate five distinct groupings: aggressive career offenders, women who killed or assaulted persons in retaliation or self-defense, women who maltreated children, substance-dependent women experiencing intimate partner violence (IPV), and social capital offenders. These findings lend support to prior research on pathways and typologies of women’s offending, and decision rules effectively “triage” cases according to most pressing needs. The model offers unique utility for researchers, practitioners, and policy makers working with women in the criminal legal system.